Design Build a 4x4 Mimo Microstrip Antenna with Artificial Dielectric Muse Array Technique to increase Antenna Gain pexisting Application 5G - Ade Silvia Handayani; Aan Sugiyanto; Ciksadan Ciksadan; Jon Endri (Program Studi Teknik Elektro Universitas Khairun, 2023)
The development of fifth-generation cellular technology, commonly referred to as